2022
DOI: 10.1186/s12859-022-04685-z
|View full text |Cite
|
Sign up to set email alerts
|

Variance of allele balance calculated from low coverage sequencing data infers departure from a diploid state

Abstract: Background Polyploidy and heterokaryosis are common and consequential genetic phenomena that increase the number of haplotypes in an organism and complicate whole-genome sequence analysis. Allele balance has been used to infer polyploidy and heterokaryosis in diverse organisms using read sets sequenced to greater than 50× whole-genome coverage. However, sequencing to adequate depth is costly if applied to multiple individuals or large genomes. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Virulence phenotypes of B. lactucae are monitored by the International Bremia Evaluation Board (99) and phenotypes of race-type isolates are established if a specific virulence phenotype is observed repeatedly in several regions over several years. Genotyping indicated that several of the type isolates were likely heterokaryotic (35,36). This is important because the phenotypes reported for these isolates were likely to be a compound of two or more genotypes, and the phenotype could change rapidly due to shifts in the nuclear population.…”
Section: Genome-enabled Track and Tracementioning
confidence: 99%
See 1 more Smart Citation
“…Virulence phenotypes of B. lactucae are monitored by the International Bremia Evaluation Board (99) and phenotypes of race-type isolates are established if a specific virulence phenotype is observed repeatedly in several regions over several years. Genotyping indicated that several of the type isolates were likely heterokaryotic (35,36). This is important because the phenotypes reported for these isolates were likely to be a compound of two or more genotypes, and the phenotype could change rapidly due to shifts in the nuclear population.…”
Section: Genome-enabled Track and Tracementioning
confidence: 99%
“…Heterothallic DMPs have higher levels of heterozygosity; sequenced DMP genomes range from 0.16% (P. effusa) to 1.71% (Sclerospora graminicola) heterozygosity, and higher levels have been reported for other oomycetes (35). Heterokaryotic and polyploid individuals tend to have higher levels of apparent heterozygosity than diploids of the same species (36). Genetic segregation during gametogenesis and subsequent fusion generates new allelic combinations, purges deleterious alleles, and exposes recessive phenotypes.…”
Section: Multiple Roads Lead To Virulencementioning
confidence: 99%